2019
DOI: 10.1021/acs.iecr.8b06094
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Novel Composite Metal Nanoparticles for Hydrogenation and Dye Degradation Applications

Abstract: Biofriendly green sustainable nanocatalyst Au@NiAg with high catalytic activity was prepared for hydrogenation and degradation of aquatic contaminants such as 4-nitrophenol (4-NP), Methyl Orange (MO), and Orange G (OG). Synthesized Au@Ni nanoparticles have a triangular shape while the Au@NiAg nanoparticles are of spherical shape and of smaller size, attributed to the digestive ripening of the Au@Ni where silver ion was deposited on the host Au@Ni nanoparticle surface. The Au@NiAg nanoparticles catalyzed hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…These diffraction peaks are perfectly indexed with face-centered cubic phase crystalline structure of NiO (Fig. 2a) [31]. The diffraction peaks exist at 13.4 o and 27.4 o which corresponds to (100), and (002) planes of bare g-C 3 N 4 (JCPDS card No-65-287), These peaks are attributed to interplanar staking of aromatic systems along with inter-layer structural packing represented in Fig.…”
Section: Dye Degradation Testmentioning
confidence: 80%
See 1 more Smart Citation
“…These diffraction peaks are perfectly indexed with face-centered cubic phase crystalline structure of NiO (Fig. 2a) [31]. The diffraction peaks exist at 13.4 o and 27.4 o which corresponds to (100), and (002) planes of bare g-C 3 N 4 (JCPDS card No-65-287), These peaks are attributed to interplanar staking of aromatic systems along with inter-layer structural packing represented in Fig.…”
Section: Dye Degradation Testmentioning
confidence: 80%
“…This result is well-matched with the JCPDS card no-04-0835. These diffraction peaks are perfectly indexed with face-centered cubic phase crystalline structure of NiO (Fig.2a)[31]. The diffraction…”
mentioning
confidence: 72%
“…After calcination, new characteristic peaks assigned to NiO and mixed metal oxide (NiAl 2 O 4 ) were observed, which suggested that the LDH phase has completely converted into LDO. When NiO and NiAl 2 O 4 were reduced under H 2 , both Ni/Ni x Al y O­(1) and Ni/Ni x Al y O­(0) exhibited three typical characteristic diffraction peaks of metallic Ni at 44.3, 51.8, and 76.4° (JCPDS: 04–0850), suggesting that most of Ni­(II) had been in situ reduced to Ni(0) . By comparison, the peaks of Ni(0) in the Ni/Ni x Al y O­(1) were much broader than that of Ni/Ni x Al y O­(0).…”
Section: Resultsmentioning
confidence: 99%
“…56 These core-shell structures possess multifunctional properties through integrating two different materials into one entity. Therefore, they are widely studied and used in various applications such as catalysis, [58][59][60][61][62][63] electronics, 64,65 biomedical applications, [66][67][68] photoluminescence, [69][70][71][72] sensors, 73 piezo-electrics, 74,75 magnetic applications, [76][77][78] energy storage, 79,80 solar cells, [81][82][83] and CO 2 capture. [84][85][86] Core-shell materials offer additional electronic modifications due to band-edge alignment at the interface between the core and shell.…”
Section: Core-shell Structuresmentioning
confidence: 99%